OPPRESSION OF WIVES AND GIRLS IN THE REPUBLIC OF UZBEKISTAN LEGAL BASIS OF PROTECTION FROM VIOLENCE (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
In this article, the opportunities created for women in our country in recent years, the legal basis for protecting women from oppression and violence and the comprehensive guarantee of their rights and freedoms, ensuring protection from all forms of oppression and violence are among the priorities of our state. is shown to be one.